PERUBAHAN PERILAKU GROOMING DAN IMOBILITAS MENCIT BALB/C TERINDUKSI DEPRESI YANG DISUPLEMENTASI TEMPE SEBAGAI SUMBER PARAPROBIOTIK - Vanessa Ardianty; Brian Saputra Manurung (Faculty of Agricultural Technology, University of Jember, 2020)
Depression, a mental disorder marked by sadness, anhedonia and increased fatigability, is becoming more common in this industry 4.0 era. Nowadays, depression affects approximately 322 million people around the world (more than 14 million in Indonesia) and gives major contribution to the rise of global burden of disease. Although antidepressant is considered the common treatment for depression, recent studies show a possibility to treat depression by altering gut microbiome of the patient, by giving them probiotic food. Tempeh is a globally well-known Indonesian paraprobiotic food which already proven to modulate gut microbiota. This research aimed to find out the effect of tempeh to depression symptom as expressed in Balb/c mice behaviors. The methods used was to feed tempeh or tempeh starter to mice which were depressed-induced by Unpredictable Chronic Mild Stress (UCMS) procedure. Parameter measured were depression level of the Balb/c mice based on immobility times and grooming durations acquired from tail suspension test, forced swim test, sucrose splash test and coat state score. The result showed that tempeh supplementation did not affect coat states and grooming durations but tend to improve immobility times of the Balb/c mice. Meanwhile, tempeh starter supplementation tends to improve the immobility time and kept coat state clean/tidy, but lowered grooming duration. In conclusion, supplementation of paraprobiotic tempeh, especially in starter form, tend to improve depression symptoms. Keywords: depression, mice, paraprobiotic, tempeh